Cation and Zn Accumulation in Brown Seeds of the Euhalophyte Suaeda salsa Improves Germination Under Saline Conditions - Guo, Jianrong (Front Plant Sci, 2020)
Salinity inhibits plant growth due to salt ion accumulation in plant cells and reduced absorption of other nutrients such as metal ions; however halophyte plants have evolved mechanisms to survive and thrive in high-salt conditions. The euhalophyte Suaeda salsa generates dimorphic seeds (black and brown), which show marked differences in germination and seedling growth under high-salt conditions. However, it is unclear whether their ionic status differs. Here, to provide insight on the role of ions in salt tolerance, we used inductively coupled plasma mass spectrometry to measure the ion contents in the dimorphic seeds from S. salsa plants treated with or without NaCl. We measured the macroelements Na, K, Mg, and Ca, and the microelements Mn, Fe, Zn, Cu, and Mo. NaCl-treated S. salsa plants produced seeds with significantly reduced metallic element contents and significantly increased Na(+) contents. The brown seeds of S. salsa plants treated with 0 and 200 mM NaCl had much higher contents of K(+), Ca(2+), and Fe(2+) compared with the black seeds. However, the S. salsa seeds (both black and brown) from NaCl-treated plants were significantly larger, and had higher germination rate and higher seedling salt tolerance compared with seeds from plants not treated with NaCl. Interestingly, we measured significantly higher Zn(2+) contents in the brown seeds from plants treated with NaCl compared with the black seeds. This suggests that the high contents of Zn(2+) and other cations affected seed development and salt tolerance during germination under high-salt conditions. These observations provide insight into the mechanisms of salt tolerance in this halophyte and inform efforts to increase salt tolerance in salt-sensitive species.